Comparative Analysis of Anthropometric Parameters as Obesity Indicators for Sixth Grade Boys from Different Regions in Montenegro - Ivana Cerkez Zovko; Milena Mitrovic; Marin Corluka (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2020)
The aim of this study was to measure the morphological characteristics and determine the nutritional levels of boys aged 11-12 years from the North, Central and Southern regions of Montenegro, as well as to compare the results, to determine whether differences in nutritional levels occur between boys living in different regions. The sample consisted of 42 sixth grade boys (11-12 years old) from Bijelo Polje (Northern Region), Podgorica (Central Region) and Budva (Southern Region). Four variables were measured in the study: body height, body weight, waist circumference and hip circumference Basic central and dispersion descriptive parameters were calculated for all variables. Obesity levels were determined using three indices: body mass index, waist-to-hip ratio index, and waist-to-height ratio index. The results showed a fairly high percentage of obesity when it comes to all three indices, however, statistically significant differences between boys from different regions occurred only when it comes to overweight and obesity according to the waist-hip ratio index and waist-to-waist ratio index. In the first case, boys from the Northern region were statistically significantly obese than the others, and in the second case, boys from the Southern region were statistically significantly more obese than boys from the other two regions. In any case, given the rather high percentage of obesity, it is necessary to take certain measures to reduce the number of obese boys in all three regions.